Intellectual capital disclosure and corporate governance: empirical evidence from a cross country that offering Islamic bank services - Syaima Adznan,; Zulkarnain Muhamad Sori,; Shamsher Mohamad Ramadili Mohd, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Intellectual capital is imperative for Islamic banks given their unique characterisctiscs in that they offer innovative Shariah-based solutions to the modern financial problems. This study therefore examined the influence of corporate goverance on intellectual capital disclosure (ICD) practices of Islamic banks. Data from a sample of 33 Islamic banks for the period 2012 to 2018 were collected. A self-developed ICD checklist was used to measure the extent of IC information disclosed in the annual report. This paper also examines the relationship between ICD practices and several corporate governance components which includes board size, board meeting, board independence, board gender, board expertise, audit committee size, audit committee meeting, audit committee independence, audit committee gender and audit committee expertise. Our results revealed that having an effective corporate governance structure is essential, as it is able to influence the ICD practices of Islamic banks. However, instead of focusing on the role of the board, our paper highlights the importance role of audit committee functions. Specifically, the results suggest that larger or reasonable audit committee size tends to have varied skills and expertise among the audit committee members, resulting in more information by allowing for greater diversity of backgrounds and viewpoints. Gender diversity in audit members’ profiles will also encourage the board to be more effective and creative in generating innovative ideas, hence more IC will be created. This study adds to the empirical studies on corporate governance from Islamic banks’ perspectives covering several countries. It also introduce the Shariah capital, as one of components in the IC index to respond to the peculiarities of Islamic on intellectual capital.